Cumulative live birth rates after IVF in patients with polycystic ovaries: phenotype matters. Issue 2 (August 2018) - De Vos, Michel; Pareyn, Stéphanie; Drakopoulos, Panagiotis; Raimundo, José M.; Anckaert, Ellen; Santos-Ribeiro, Samuel; Polyzos, Nikolaos P.; Tournaye, Herman; Blockeel, Christophe
Abstract: Research question: Do cumulative live birth rates (CLBR) vary among women with different polycystic ovary syndrome (PCOS) phenotypes who undergo IVF/intracytoplasmic sperm injection (ICSI) treatment? Design: In this retrospective cohort study, data from 567 patients undergoing an assisted reproductive technology (ART) cycle between January 2010 and December 2015 were collected. Demographical traits, cycle characteristics and clinical and laboratory data were analysed. Results: After conventional ovarian stimulation using a gonadotrophin-releasing hormone antagonist protocol, the median number of oocytes retrieved ranged between 11 and 13.5 and did not differ significantly among the studied groups. Live birth rate (LBR) after fresh embryo transfer and CLBR after transfer of all fresh and vitrified embryos were significantly lower in women with hyperandrogenic PCOS phenotypes A (LBR 16.7%, CLBR 25.8%) and C (LBR 18.5%, CLBR 27.8%) compared with women with normoandrogenic PCOS phenotype D (LBR 33.7%, CLBR 48%) ( P -value for LBR 0.01 and 0.03, respectively; P -value for CLBR 0.002 and 0.01, respectively) and controls with a polycystic ovarian morphology (LBR 37.1%, CLBR 53.3%) ( P -value for LBR 0.002 and 0.01, respectively; P -value for CLBR <0.001 and 0.001, respectively). Multivariate regression analysis indicated that after adjustment for relevant confounders, PCOS phenotype was an independent predictor for CLBR. Conclusions: Hyperandrogenic PCOS phenotypes confer significantly lower CLBR compared with their normoandrogenic counterparts. These findings may imply the need for adapted counselling and tailored approaches when treating PCOS patients with hyperandrogenism who require ART.